2019
DOI: 10.5187/jast.2019.61.4.192
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilization, nutrient digestibility and bone quality of broiler chickens fed Tanzania-type diets in different forms with enzymes

Abstract: A study was conducted to determine the influence of feed form and microbial enzyme supplementation on energy utilization, bone quality, and amino acid and mineral digestibility of broiler chickens. Four hundred and eighty Ross 308, day-old broiler chickens were randomly assigned to eight diets formulated from commonly used ingredients in Tanzania. A 2 (pellet or mash) × 4 (control, Axtra XB, Quantum Blue (QB) and Axtra XB + QB enzyme) factorial array in a completely randomized design having six replicates per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In parallel, the global trend for reducing antibiotic growth promoters in the animal production has gathered momentum ( Pourabedin et al, 2015 ). It is particularly important to explore the nutritional interventions for the prevention of these pathological processes, and the supplementation of exogenous amylase, protease, or other enzymes for broiler diets could be a strategic approach ( Chang’a et al, 2019 ; Córdova-Noboa et al, 2021 ). Studies have shown that a number of Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the global trend for reducing antibiotic growth promoters in the animal production has gathered momentum ( Pourabedin et al, 2015 ). It is particularly important to explore the nutritional interventions for the prevention of these pathological processes, and the supplementation of exogenous amylase, protease, or other enzymes for broiler diets could be a strategic approach ( Chang’a et al, 2019 ; Córdova-Noboa et al, 2021 ). Studies have shown that a number of Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%